Answer: x = 3, y = -2 → (3, -2)
Explanation:
Using Elimination Method, multiply the equations by a number that allows the coefficients of either x or y to be the same number with opposite signs. Then add the two equations to solve solve for the remaining variable.
I choose to eliminate x:
2x - 5y = 16 --> 3(2x - 5y = 16) --> 6x - 5y = 48
3x + 2y = 5 --> -2(3x + 2y = 5) --> -6x - 4y = -10
-19y = 38
÷19 ÷19
y = -2
Next, substitute y = -2 into either equation to solve for x.
I choose the 1st equation:
2x - 5y = 16
2x - 5(-2) = 16
2x + 10 = 16
2x = 6
x = 3
Check your answer by inputting x = 3 and y = -2 into the other (2nd) equation:
3x + 2y = 5
3(3) + 2(-2) = 5
9 + -4 = 5
5 = 5